Analisis Fusan Hasil Fusi Protoplas Intraspesies Pichia manshurica DUCC-015 (Analysis of Fusant from Protoplast Fusion Intraspecies of Pichia manshurica DUCC-015) - Roslenawati, Roslenawati; Kusumaningrum, Hermin Pancasakti; Pujiyanto, Sri (JURNAL SAINS DAN MATEMATIKA, 2014)
The intraspecies protoplast fusion of P. manshurica DUCC-015 was conducted in searching the fusant with greater inulinase production. Inulinase on Dahlia variabilis Willd tuber from Baturraden-Purwokerto showed inulinase activity 0,683 IU/mL. Inulinase is an enzyme that catalyzes the hydrolysis reaction of inulin polysaccharides into fructose and or fructooligosacarides. The aims of this research was revealing fusant from intraspecies protoplast fusion process of P. manshurica DUCC-015 followed by analyzing of their inulinase productivity and activity. The research metodology protoplast fusion process consist of lysis of cell wall, protoplast fusion and regeneration of intraspecies fusant P. manshurica DUCC-015. Analysis of fusant were done by Schiff Basic Fuchsin staining of fusant nuclei, also measuring the inulinase activity and inulinase production comparing with their parent. The inulinase activity will be analyzed by T-Test Independent Two Sample on 95% Confidence interval of the difference use Statistical Product and Service Solution programme (SPSS). The result of experiment gaining fusant with regeneration capability, ploidi diversity of fusant, inulinase activity about 0,965 IU/mL while their parent 0,622 IU/mL and inulinase production 0,736 IU/mL comparing with 0,731 IU/mL during 42 hours incubations. The fusant indicated the increase of inulinase activity and production compared with their parent. Keywords: Pichia manshurica DUCC-015, fusant, inulinase Fusi protoplas intraspesies Pichia manshurica DUCC-015 telah dilakukan untuk mencari fusan dengan produksi inulinase yang lebih tinggi. Inulinase pada umbi tanaman Dahlia variabilis Willd dari Baturraden-Purwokerto memperlihatkan aktivitas sebesar 0,683 IU/mL. Inulinase merupakan enzim yang mengkatalisis reaksi hidrolisis polisakarida inulin menjadi fruktosa dan atau fruktooligosakarida. Penelitian ini bertujuan untuk mendapatkan fusan hasil fusi protoplas intraspesies P. manshurica DUCC-015 yang memiliki aktivitas inulinase lebih tinggi. Rancangan percobaan fusi protoplas terdiri dari isolasi protoplas, fusi protoplas dan regenerasi fusan. Analisis fusan menggunakan pewarnaan Fuchsin pada inti sel, mengukur aktivitas dan produksi inulinase fusan. Aktivitas inulinase dianalisis dengan Uji T Test Dua Sampel Independen pada taraf kepercayaan 95% menggunakan program Statistical Product and Service Solution (SPSS). Hasil penelitian menunjukkan fusi protoplas intraspesies P. manshurica DUCC-015 menghasilkan aktivitas inulinase mencapai 0,965 IU/mL dibandingkan induk sebesar 0,622 IU/mL dan produksi inulinase 0,736 IU/mL pada inkubasi selama 42 jam. Fusan mengindikasikan kenaikan aktivitas dan roduksi inulinasi dibandingkan induk. Kata kunci : Pichia manshurica DUCC-015, fusan, inulinase.